2004
DOI: 10.2187/bss.18.7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Toxicity on Visceral Organs of Medaka Fish, Oryzias latipes: Aiming to Raise Fish from Egg to Egg in Space

Abstract: Histological survey was made to determine nitrate toxicity on the Medaka fish, Oryzias latipes. In order to investigate the effects of short-term exposure to nitrate, one-month-old Medaka fish was exposed to NaNO 3 at concentrations of 100 and 125 mg NO 3 -N l -1 for 96 hours. At the end of the exposure period, survival rate was found to be 30% and 10%, for the 100 and 125 mg NO 3 -N l -1 exposure concentrations, respectively. Histological examination of the organs showed that disruption of cell alignment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
(11 reference statements)
1
8
0
Order By: Relevance
“…Common carp Cyprinus carpio exposed to 12 mg/L nitrate-N presented abrupt and sluggish swimming movements, with occasional jumping and hitting the walls (Iqbal et al, 2005). Shimura et al (2004) observed loss of appetite and lethargic behavior in juvenile medaka O. latipes exposed to 100 mg/L nitrate-N. Our results showed a significantly lower final weight and SGR in the high-nitrate 157.3 mg/L treatment. Significant reduction in weight or body size in response to a stressor may indicate that energy is being used in detoxification rather than growth.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Common carp Cyprinus carpio exposed to 12 mg/L nitrate-N presented abrupt and sluggish swimming movements, with occasional jumping and hitting the walls (Iqbal et al, 2005). Shimura et al (2004) observed loss of appetite and lethargic behavior in juvenile medaka O. latipes exposed to 100 mg/L nitrate-N. Our results showed a significantly lower final weight and SGR in the high-nitrate 157.3 mg/L treatment. Significant reduction in weight or body size in response to a stressor may indicate that energy is being used in detoxification rather than growth.…”
Section: Discussionsupporting
confidence: 50%
“…Common carp Cyprinus carpio exposed to 12 mg/L nitrate‐N presented abrupt and sluggish swimming movements, with occasional jumping and hitting the walls (Iqbal et al, ). Shimura et al () observed loss of appetite and lethargic behavior in juvenile medaka O. latipes exposed to 100 mg/L nitrate‐N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, not clear what the biological effects of changes in water quality were. Water quality seems to be seldom, if ever, monitored in space flights (Shimura et al, 2004). Our study is the first to attempt to examine water quality in ground‐based studies of SMG exposure on teleosts and suggests that such measures deserve more attention in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposition demands large amounts of oxygen and produces large quantities of ammonia and NO 3 − (de Croux, Julieta & Loteste 2004). Municipal and industrial wastes are concentrated sources of nitrogen compounds that are, to a large extent, released directly into surface waters (Shimura, Ma, Ijiri, Nagaoka & Uchiyama 2004). Even if treated, this waste will represent a heavy water pollution load since secondary treatment removes less than half of the nitrogen (Jittawattanarat, Kostarelos & Khan 2007).…”
Section: Introductionmentioning
confidence: 99%